Application of the Multicomponent Spectral Fitting Algorithm in the Estimation of the Correct Value of Phosphorus determined by ICP OES in Soil Samples - Santos, Lenio Da Silva; Bley, Henrique; Selau, Lisiane Priscila Roldão; Tiecher, Tales; Gianello, Clesio (Communications in Soil Science and Plant Analysis, 2019)
Phosphorus (P) determination by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) in soil extracts is affected by copper (Cu) content and may lead to misinterpretation of the results. In this study, Multicomponent Spectral Fitting (MSF) method for the quantitative determination of P in the presence of Cu was tested. Phosphorus determination by UV/Vis molecular absorption spectrometry (COL) was free from copper interference. Phosphorus determination by ICP OES at wavelengths of 213.618 and 214.914 nm without use of MSF were subject to interference when Cu concentration was greater than 1.5 and mg L −1 and 3.5 mg L −1 , respectively. When the P: Cu ratio in solution was 1:1 and 2:1, on average, there was no significant difference between the P determined by COL and by ICP-OES using MSF. In matrices containing Cu, it is indicated to use the P spectral line at 214.914 nm because it was less sensitive to Cu concentration than spectral line at 213.618 nm.